STRATEGI KEPALA SEKOLAH DALAM IMPLEMENTASI KURIKULUM MERDEKADI SMA AL AMIN - Rahmawati, Ima; Hasanah, Siti Lutfiatul (JOURNAL EDUCATIONAL MANAGEMENT REVIEWS AND RESEARCH, 2024)
This study aims to analyze the principal's strategy in the implementation of the Independent Curriculum at Al Amin High School. The Independent Curriculum, which is designed to provide freedom and uniqueness in the learning process, demands significant changes in education management. The research method used is qualitative with a case study approach, where data is collected through interviews, observations, and documentation. The results of the study show that school principals implement several key strategies, namely: (1) a clear vision of joint development regarding the Independent Curriculum, (2) training and professional development for teachers to understand and implement the curriculum, (3) the creation of a conducive learning environment, and (4) collaboration with various parties, including parents and the community. This finding is expected to provide insight for school principals and other stakeholders in an effort to implement the Independent Curriculum more effectively, as well as encourage the improvement of the quality of education at Al Amin High School.